Divanillin-Based Aromatic Amines: Synthesis and Use as Curing Agents for Fully Vanillin-Based Epoxy Thermosets - Savonnet, Etienne; Le Coz, Cedric; Grau, Etienne; Grelier, Stéphane; Defoort, Brigitte; Cramail, Henri (Frontiers in Chemistry, 2019)
Bio-based aromatic diamines from vanillin substrate were successfully synthesized and characterized. These amines, i.e., methylated divanillylamine (MDVA) and 3,4-dimethoxydianiline (DMAN), were then tested as curing agents for the design of bio-based epoxy thermosets. The epoxy thermosets obtained from these novel vanillin-based amines exhibited promising thermomechanical properties in terms of glass transition temperature and char residue.